2015
DOI: 10.1158/1055-9965.epi-14-1079
|View full text |Cite
|
Sign up to set email alerts
|

Survival among HIV-Infected and HIV-Uninfected Individuals with Common Non–AIDS-Defining Cancers

Abstract: Background Non-AIDS-defining cancers increasingly contribute to mortality among human immunodeficiency virus (HIV)-infected individuals. However, few studies have compared cancer prognosis by HIV status with adjustment for risk factors. Methods We conducted a cohort study of HIV-infected and HIV-uninfected adults in Kaiser Permanente California during 1996–2011, following subjects diagnosed with Hodgkin lymphoma (HL) or anal, prostate, colorectal, or lung cancers. We used Kaplan-Meier curves and Cox regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
82
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(87 citation statements)
references
References 41 publications
4
82
0
1
Order By: Relevance
“…Even though pre-cART data suggested poorer prognosis for PLWHIV with LC [52,53,54,55], studies focusing in the post-cART era after 1996 found no significant differences in survival rates for PLWHIV [8,43,44,47,56]. The improved outcome is most likely related, in part, to the better overall health of PLWHIV, but also to the better care since having overcome several uncertainties and worries of the first years of the HIV epidemic.…”
Section: Clinical Characteristicsmentioning
confidence: 99%
“…Even though pre-cART data suggested poorer prognosis for PLWHIV with LC [52,53,54,55], studies focusing in the post-cART era after 1996 found no significant differences in survival rates for PLWHIV [8,43,44,47,56]. The improved outcome is most likely related, in part, to the better overall health of PLWHIV, but also to the better care since having overcome several uncertainties and worries of the first years of the HIV epidemic.…”
Section: Clinical Characteristicsmentioning
confidence: 99%
“…Therapy of colorectal carcinoma is not different in HIV-positive compared to HIV-negative patients. After adjustment for age, race/ethnicity, sex, TNM stage, cancer treatment type, and smoking, cancer-related mortality was not statistically different with regards to colorectal cancer (HR 1.4, 95% confidence interval 0.8-2.7) in the Kaiser Permanente California cohort during 1996-2011 [34]. However, as stated earlier, in other cohorts adjusted cancer-specific mortality was significantly elevated for colorectum cancer (HR 1.49) [4,35], but with a rather small effect comparable to the HR shown in other cohorts.…”
Section: Colorectal Carcinomamentioning
confidence: 91%
“…In an Italian cohort, cancer of the liver Non-AIDS-defining cancer in general SIR 2.2-4 [8,9]; SIR in men increased [37], increasing [30,34,38] a All values significant. GI = gastrointestinal, aOR = adjusted odds ratio, HR = hazard ratio, PY = person years, SIR = standardized incidence ratio.…”
Section: Liver and Biliary Tract Cancermentioning
confidence: 99%
“…Results from the Kaiser Permanente cohort California showed a non-significant reduction in 5-year survival for HIV-infected subjects with prostate cancer compared to HIV-uninfected men (86% vs. 92%) [52]. Notably, after adjustment for age, race/ethnicity, sex, TNM stage, cancer treatment type, and smoking, cancerrelated mortality was higher among HIV-infected compared with HIV-negative subjects (hazard ratio (HR) 2.1).…”
Section: Presentation and Prognosismentioning
confidence: 99%